An overview of online resources for intra-species detection of gene duplications - Zhang, Xi; Smith, David Roy (Frontiers in Genetics, 2022)
Gene duplication is an important evolutionary mechanism capable of providing new genetic material for adaptive and nonadaptive evolution, but detecting duplicate genes from genomic data can be challenging. Various bioinformatics resources have been developed to identify duplicate genes from single and/or multiple species. Here, we summarize the metrics used to measure sequence identity among gene duplicates within species, compare several computational approaches that have been used to predict gene duplicates, and review recent advancements of a Basic Local Alignment Search Tool (BLAST)-based web tool and database, which allows users to conveniently explore potential homologous sequences of interest within species. This article is intended to be a quick reference guide for research tools used for detecting gene duplicates.